Increases in muscle sympathetic nerve activity, heart rate, respiration, and skin blood flow during passive viewing of exercise - Brown, Rachael; Kemp, Ursula; Macefield, Vaughan G. (Frontiers in Neuroscience, 2013)
The cardiovascular and respiratory effects of exercise have been widely studied, as have the autonomic effects of imagined and observed exercise. However, the effects of observed exercise in the first person have not been documented, nor have direct recordings of muscle sympathetic nerve activity (MSNA) been obtained during observed or imagined exercise. The aim of the current study was to measure blood pressure, heart rate, respiration, skin blood flow, sweat release and muscle sympathetic nerve activity (via microelectrodes inserted into the common peroneal nerve), during observation of exercise from the first person point of view. It was hypothesised that the moving stimuli would produce robust compensatory increases in the above-mentioned parameters as effectively as those generated by mental imagery and - to a lesser extent - actual exercise. Nine subjects watched a first-person running video, allowing them to view the action from the perspective of the runner rather than viewing someone else perform the exercise. On average, statistically significant increases from baseline during the running phase were seen in heart rate, respiratory rate, skin blood flow and burst amplitude of muscle sympathetic nerve activity. These results suggest that observation of exercise in the first person is a strong enough stimulus to evoke “physiologically appropriate” autonomic responses that have a purely psychogenic origin.